Improving immunotherapy for the treatment of hepatocellular carcinoma: learning from patients and preclinical models - Romain Desert; Fabio Gianonne; Antonio Saviano; Yujin Hoshida; Mathias Heikenwälder; Pierre Nahon; Thomas F. Baumert (npj Gut and Liver)
Abstract Hepatocellular carcinoma (HCC), the third cause of cancer-related deaths worldwide, continues to present significant therapeutic challenges. Despite significant therapeutic advancement in the last decade, the efficacy of systemic treatments for patients with advanced HCC remains unsatisfactory. While the clinical introduction of immune checkpoint inhibitors has improved response rates and overall survival, their clinical success remains still limited. Here we provide a comprehensive review of current and emerging strategies aimed at enhancing the efficacy of immunotherapy for the treatment of HCC. Both clinical studies conducted in patients as well as studies in preclinical models have markedly advanced our understanding of resistance as well as uncovered novel approaches to overcome resistance. Recent progress is paving the way for improved efficacy and safety of novel approaches that will improve the dismal prognosis of patients with advanced HCC.